HOX Antisense lincRNA HOXA-AS2 Promotes Tumorigenesis of Hepatocellular Carcinoma - Fuqiang Wang; Huili Yang; Zhigang Deng; Yongjie Su; QinLiang Fang; Zhenyu Yin (Cellular Physiology and Biochemistry, 2016)
Background: Recent studies reveal that long non-coding RNAs (LncRNAs) play critical roles in the proliferation and migration of human cancer. Previous report has shown that LncRNA HOXA-AS2 was involved in carcinoma processes. However, the expression and biological function of HOXA-AS2 in hepatocellular carcinoma (HCC) are poorly understood. Methods: Quantitative real-time PCR (qRT-PCR) was performed to detect the expression of HOXA-AS2 in HCC tissues and cell lines. The relation between lncRNA HOXA-AS2 expression and clinicopathological characteristics was assessed by chi-square test. The prognosis was analyzed using Kaplan-Meier method, and compared differences between the two groups by log-rank test. The biological function of HOXA-AS2 on HCC cells were determined both in vitro and in vivo. Results: In the present study, we found that HOXA-AS2 expression was increased in HCC tissues and adjacent normal tissues and high HOXA-AS2 expression was associated with bigger tumor size, advanced tumor stage, and shorter survival time. Knockdown of HOXA-AS2 significantly inhibited HCC cell proliferation and invasion and resulted in an increase of apoptosis. Furthermore, inhibition of HOXA-AS2 in HCC cells significantly repressed tumorigenicity in nude mice. Conclusion: Our results indicated that the inhibition of HOXA-AS2 in HCC cells significantly inhibited cell proliferation in vitro and in vivo, which might provide a potential possibility for targeted therapy of HCC.